Two-Dimensional Closed Conjugated Covalent Organic Polymers for Oxygen Reduction Reaction - Li, Yang; Peng, Peng; Huo, Feng; Shao, Xiaohong; Xiang, Zhonghua (Frontiers in Materials, 2019)
Two-dimensional Covalent Organic Polymers (COPs) which are used to catalyze oxygen reduction reaction (ORR) in regenerative fuel cells have been researched by efforts. However, due to the lack of closed conjugated molecular structures, most pyrolysis-free COPs demonstrate limited catalytic performance. In this work, four alternative COPs containing different conjugated π-bonds are designed (termed as COP-Bn, n=3, 4, 5, 6) and studied based on Charge Density Analysis, Density of States (DOS), Band Structure Analysis, First-principle and Density Functional Theory (DFT) calculations towards catalyzing ORR. Our outcomes reveal that COPs with larger conjugated structures (e.g. COP-B5 and COP-B6) can achieve higher activity during ORR catalysis.